Indonesian Journal of Obstetric and Gynecology (INAJOG), Vol.6 No.1 page 1-68 January 2018 - Perkumpulan Obstetri Dan Ginekologi Indonesia (POGI, 2018)
- Effectiveness of oral probiotics (lactobacillus rhamnosus Gr-1 and lactobacillus reuteri RC-14) as adjuvant therapy in reproductive aged women with vaginal discharge - The Association between menstruasi disorder and work disturbance among employees - The Association of C-reactive protein levels in secon trimester of pregnancy with preeclampsia - ...